Analisis Kadar Kofein Kopi Luwak Dengan Variasi Jenis Kopi, Spesies Luwak Dan Cara Pengolahan Dengan Metoda TlC Scanner - Rahma Yulia; Adek Zamrud Adnan; Deddi Prima Putra (Fakultas Farmasi Universitas Andalas, 2016)
Caffeine analysis from Luwak coffee in different types of coffees, Luwak species and processed by using TLC Scanner method had been done. 8 samples of Luwak coffee, that is R.Ab.K ; R.Ab.B ; R.Ph.K ; R.Ph.B ; A.Ab.K ; A.Ab.B ; A.Ph.K ; A.Ph.B which were extracted by dichloromethane (DCM). TLC separation had been done through stationary phase with silica gel GF254 and mobile phase are solute of dichloromethane (DCM) : methanol (9,5 : 0,5). Caffeine content had been counted by using regression equality y = 2715,112 + 4,389x and giving percentage in succession 1,91 ; 2,04 ; 1,30 ; 1,89 ; 1,29 ; 1,45 ; 1,25 ; 1,42 %. The highest of caffeine had been given by Robusta coffee which has been given before to A. binturong luwak and processed wetly 2,04 %. The lowest of caffeine content had been given to Arabica coffee which has been given before to P. hermophroditus luwak 1,25 %. Three way – Anova statistic SPSS 21 tabulation had showed the result that the kind of coffee, variety of Luwak and the way of processing gave significant value toward caffeine content in p < 0,05.